Boron rich solids sensors, ultra high temperature ceramics, thermoelectrics, armor - Orlovskaya, Nina; Lugovy, Mykola (NATO Science for Peace and Security Series B: Physics and Biophysics, 2011)
Theobjective of this book is to discuss the current status of research and development of boron-rich solids as sensors, ultra-high temperature ceramics, thermoelectrics, and armor. Novel biological and chemical sensors made of stiff and light-weight boron-rich solids are very exciting and efficient for applications in medical diagnoses, environmental surveillance and the detection of pathogen and biological/chemical terrorism agents. Ultra-high temperature ceramic composites exhibit excellent oxidation and corrosion resistance for hypersonic vehicle applications. Boron-rich solids are also promising candidates for high-temperature thermoelectric conversion. Armor is another very important application of boron-rich solids, since most of them exhibit very high hardness, which makes them perfect candidates with high resistance to ballistic impact. The following topical areas are presented: boron-rich solids: science and technology; synthesis and sintering strategies of boron rich solids; microcantilever sensors; screening of the possible boron-based thermoelectric conversion materials; ultra-high temperature ZrB2 and HfB2 based composites magnetic, transport and high-pressure properties of boron-rich solids; restrictions of the sensor dimensions for chemical detection; armor.